What Indonesian Think of Japanese’s Compliment - Kusumawati, Mutia (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
A compliment is one of the positive politeness strategies that had a function to bring closer the relationship between the speaker and the receiver. However, the characteristics and rules of using compliments differ based on language. Nowadays, communication opportunities between Indonesians and the Japanese had been increasing. If there any differences regarding compliments in Indonesian and Japanese, then problems that make human relationships not well-formed potentially occur. Therefore, this study aims to find out what problems are experienced by Indonesian regarding compliments in communication with Japanese, then find out what kind of action needs to take to avoid these problems. To find out the things mentioned above, the researcher conducted interviews with five respondents and distributed questionnaires based on the interview result to 60 respondents. The results of the interview and questionnaires show that Indonesians sometimes feel that the Japanese often giving compliments, and those compliments are excessive. When receiving compliments, Indonesians sometimes feel confused because they feel the object of compliment is not worthy of it, and they do not know how to respond. Moreover, Indonesians rarely feel confused when they try to give compliments to Japanese, but often feel like a failure after that. Hens, these thoughts can contribute to communication breakdown. These problems can be attributed to compliment factors and strategies. Hens, it is necessary to provide understanding to both speakers of the language that different factors that support the emergence of compliment and the use of compliment strategies.